PENERAPAN AKUNTANSI PERTANGGUNGJAWABAN PADA PUSAT BIAYA SEBAGAI ALAT PENILAIAN KINERJA MANAJER DI PT. PERKEBUNAN NUSANTARA IX - SAFI'I, IMAM (Jurnal Akuntansi AKUNESA, 2015)
Accountancy of responsibilities significant in the company because content information about income, cost connection with a part or unit in the company. Every cost center responsibilities for cost apply by ministry, which report manage center of cost to serve with comparison had arrange with budget realization. Goals you want in this research is to determine the accountancy of responsibilities at the expenses cntre as a performance assessment tool in PT Perkebunan Nusantara IX (Persero).Keywords : Accountancy of responsibilities, cost center, performance assessment